2021
DOI: 10.1080/14756366.2021.1917564
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary sulphonamide derivatives as dual acting small molecules that inhibit LSD1 and suppress tubulin polymerisation against liver cancer

Abstract: A series of tertiary sulphonamide derivatives were synthesised and evaluated for their antiproliferative activity against liver cancer cell lines . Among these tertiary sulphonamides, compound 17a displayed the best anti-liver cancer activity against Bel-7402 cells with an IC 50 value of 0.32 lM. Compound 17a could effectively inhibit tubulin polymerisation with an IC 50 value of 1.27 lM. Meanwhile, it selectively suppressed LSD1 with an IC 50 value of 63 nM. It also concentration-dependently inhibited migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Recently, two dual-target LSD1/HDACs inhibitors, 4SC-202 and JBI-802, have entered clinical trials to evaluate their efficacy, safety, and tolerability, proving the feasibility of multitarget drugs based on LSD1. The multitarget inhibitors related to LSD1 and their design strategies in recent years are also reviewed, while most of them exhibited moderate enzyme inhibitory activity and are still faced with common challenges, such as toxicity, PK, and PD after entering clinical trials. In addition, Groves et al discovered that LSD1 degrader UM171 and HDAC inhibitors exhibit a synergistic inhibitory effect on DIPGs cells, indicating the scope of multitarget drugs extends beyond inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two dual-target LSD1/HDACs inhibitors, 4SC-202 and JBI-802, have entered clinical trials to evaluate their efficacy, safety, and tolerability, proving the feasibility of multitarget drugs based on LSD1. The multitarget inhibitors related to LSD1 and their design strategies in recent years are also reviewed, while most of them exhibited moderate enzyme inhibitory activity and are still faced with common challenges, such as toxicity, PK, and PD after entering clinical trials. In addition, Groves et al discovered that LSD1 degrader UM171 and HDAC inhibitors exhibit a synergistic inhibitory effect on DIPGs cells, indicating the scope of multitarget drugs extends beyond inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compound 14 exhibited significant inhibitory effects on tubulin polymerization (IC 50 = 1.3 μM) and LSD1 activity (IC 50 = 63 nM) in a concentration-dependent manner. Further studies in vivo on Bel-7402 cell xenograft mouse model demonstrated that intragastric administration of compound 14 resulted in a significant reduction in tumor weight without any observable toxicity to the global organs …”
Section: Co-inhibitors Of Lsd1 and Other Targetsmentioning
confidence: 99%
“…Recently, novel small molecule inhibitors against LSD1, such as coumarin analogues and benzofuran derivatives, have been synthesized and can be utilized for targeting the cellular activity of LSD1 [69,70]. Moreover, tertiary sulphonamide derivatives exhibiting dual properties of inhibition of tubulin polymerization and LSD1 inhibition have recently been implicated as potential treatment for liver cancer [71].…”
Section: Lsd1 Inhibition As a Treatment Strategy For Liver Cancermentioning
confidence: 99%